2014
DOI: 10.5713/ajas.2014.14072
|View full text |Cite
|
Sign up to set email alerts
|

Seamustard (<i>Undaria pinnatifida</i>) Improves Growth, Immunity, Fatty Acid Profile and Reduces Cholesterol in Hanwoo Steers

Abstract: The study was designed to evaluate the effect of 2% seamustard (Undaria pinnatifida) by-product (SW) on growth performance, immunity, carcass characteristics, cholesterol content and fatty acid profile in Hanwoo steers. A total of 20 Hanwoo steers (ave. 22 months old; 619 kg body weight) were randomly assigned to control (basal diet) and 2% SW supplemented diet. Dietary SW supplementation significantly (p<0.05) improved average daily gain and gain:feed ratio as well as serum immunoglobulin G concentration. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…Overall, the seaweed formulated diet was found to improve growth, immunity, and fatty acid profile and was helpful in reducing cholesterol levels in beef (Hwang et al, 2014). In another study, Or-Rashid et al (2008) reported that supplementing the diet with seaweed meal alters the ruminal trans-18:1 fatty acid and conjugated linoleic acid composition in cattle.…”
Section: Beef and Dairy Cattlementioning
confidence: 94%
See 3 more Smart Citations
“…Overall, the seaweed formulated diet was found to improve growth, immunity, and fatty acid profile and was helpful in reducing cholesterol levels in beef (Hwang et al, 2014). In another study, Or-Rashid et al (2008) reported that supplementing the diet with seaweed meal alters the ruminal trans-18:1 fatty acid and conjugated linoleic acid composition in cattle.…”
Section: Beef and Dairy Cattlementioning
confidence: 94%
“…Supplemented diets adequately improved the rumen fermentation and digestion in cows and influenced the quality of milk and meat in cattle (Bendary et al, 2013;Hwang et al, 2014). In most of the studies, dietary inclusion of even a small amount of seaweed or its components enhanced the nutritional value of feed and improved the performance of the targeted animals.…”
Section: Applications Of Seaweeds As Animal Feedmentioning
confidence: 99%
See 2 more Smart Citations
“…Fucoidans are branched polysaccharide sulfate esters extracted from the cell wall of marine algae, containing l-fucose as one of the major monosaccharides [9] and they have been shown to have antibacterial [6], immunomodulating [10] and antioxidant [11] activities. Previous researches suggested that E. cava can be used as environment friendly substitutes for antibiotics in diets to improve growth in fishes [12] and the immune systems of animals [13]. However, as per our knowledge, not much work has been done to utilize E. cava as feed additive for pigs.…”
Section: Introductionmentioning
confidence: 99%